Information communication technology and supply chain efficiency in manufacturing SMES in Bulawayo Province in Zimbabwe - Bafana, Sithokozile (Logistics, supply chain, sustainability and global challenges, 2024)
There has been a global plummeting trend of failure in most manufacturing Small and Medium Enterprises (SMEs) due to purported supply chain inefficiency. It is imperative for clothing manufacturing SMEs in developing nations like Zimbabwe, with reference to Bulawayo Province, which lacks digitization to integrate Information and Communication Technology (ICT) solutions into their supply chain operations to improving efficiency and maintain competitiveness in the global market. Thus, the purpose of the study was to evaluate ICT and supply chain efficiency in the clothing manufacturing SMEs in Bulawayo Province. Employing the pragmatic approach, data were collected using semi-structured questionnaires from a sample of 107 from a total population of 147 that were triangulated with 15 interviews from clothing manufacturing SMEs in Bulawayo. A simple linear regression analysis through Ordinary Least Squares was conducted to test the relationship between ICT and supply chain efficiency. The results show that ICT has a positive and statistically significant effect on cost performance, agility and delivery performance in Bulawayo clothing manufacturing SMEs. By prioritizing ICT adoption, managers can achieve better cost management, increased responsiveness to market demands, and enhanced delivery capabilities. It is recommended that clothing manufacturing SMEs in Bulawayo should embrace the ICT. Further studies should examine the relationship between ICT and supply chain efficiency in manufacturing SMEs across different industries and nations.
Keywords: informacijska in komunikacijska tehnologija; information and communication technology; material requirement planning; MSP (mala in srednje veliak pdojetja); načrtovanje potreb po materialu; SMEs (small and medium enterprises); supply chain efficiency; učinkovitost dobavne verige